Bilateral vasculopexy of anomalous vertebral arteries causing cervicomedullary compression: case report and technical note - Shah, Abhidha (Springer-Verlag, 2012)
INTRODUCTION: The authors report an extremely rare cause of cervicomedullary cord compression by anomalous ectatic vertebral arteries. MATERIAL: A 50-year-old male patient presented with a 9 month history of progressive quadriparesis. Investigations revealed that the vertebral arteries on both sides had a mirror-like course and caused a deep indentation into the high cervical cord. Bilateral vasculopexy was done using Teflon slings. The treatment resulted in rapid recovery from symptoms. CONCLUSIONS: Anomalous course of the vertebral artery can result in symptoms of high cervical cord compression. Vasculopexy can result in lasting cure from symptoms.